Tin star - Castellucci, Cecil 1969- (Roaring Brook Press, 2014)
"Beaten and left for dead, fourteen-year-old Tula Bane finds herself abandoned on a space station called Yertina Feray after traveling with the colonist group, Children of the Earth"..